Monoclonal immunoglobulins on red blood cells: a potential supplementary diagnostic indicator for monoclonal gammopathies - Bing, Benxia; Yang, Xiaowei; Wang, Chenghua; Xu, Liang; Cheng, Shiqing; Liu, Yun; Wang, Qiuhan; Zhai, Chunjuan; Zhao, Bing; Wang, Rong; Sun, Jing (Frontiers in Immunology, 2025)
IntroductionRed blood cells (RBCs) have the capability to bind and transport a variety of substances. The aim of this study is to investigate the potential of circulating RBCs as carriers of monoclonal immunoglobulins (M proteins).MethodsPatients who were newly diagnosed with monoclonal gammopathy in the Nephrology Department of Shandong Provincial Hospital affiliated with Shandong First Medical University from April 2023 to December 2024 were included in this study. Western blots were performed on RBC membrane proteins using primary antibodies against human IgG, IgM, IgA, kappa, and lambda.ResultsForty-nine patients with monoclonal gammopathy were enrolled in this study. Substantial increases in the amounts of erythrocyte-bound immunoglobulins, characterized by monoclonal properties, were observed. Among the 49 patients, 45 (91.8%) had M proteins detected on RBCs, 38 (77.6%) had abnormal serum capillary electrophoresis and immunosubtraction (CE/IS) results, 36 (75.3%) had abnormal serum free light-chain (sFLC) ratios, and 32 (65.3%) had abnormal serum total light-chain (sTLC) ratios. 53.1% (26/49) of patients with monoclonal gammopathy had concordant results between erythrocyte Western blot and CE/IS. 22.4% (11/49) of patients had negative serum CE/IS results but extrinsic monoclonal immunoprotein bands on RBCs, which were consistent with the findings from sFLC, bone marrow flow cytometry, or renal histopathology. 16.3% (8/49) of patients had abnormal but inconsistent results between serum CE/IS and erythrocyte electrophoresis. Four (8.2%) patients had no or polyclonal immunoprotein bands on RBCs.ConclusionMonoclonal immunoglobulins were presented on erythrocytes, which may serve as a supplementary diagnostic indicator for the detection of M proteins.